Attention : from theory to practice - Kramer, Arthur F.; Wiegmann, Douglas A.; Kirlik, Alex (Oxford series in human-technology interaction, 2007)
I. Toward a practical view of attention: theoretical and methodological issues ; II. Emerging issues in applied attention theory ; III. Attention and driving ; IV. Attention and aging ; V. Attention and interface design ; VI. Attention and training ; VII. Future directions.